2023
DOI: 10.5114/ada.2023.128999
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis and gestational age – is there an association between them? A review of the literature and an analysis of pathology

Abstract: Introduction The connection between prematurity and atopic dermatitis (AD) is an intensively investigated topic with existing knowledge gaps. The last review with a meta-analysis in this field was published in 2018. Since then, there have been great advances in the comprehension of AD pathophysiology. Aim To update the knowledge and to discuss the recent findings in the field of AD and its association with prematurity in light of the newest publications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…In our study, prematurity was positively related to the future development of asthma and AR in the pediatric population, while being protective against the development of AD. These results are consistent with ndings from other nationwide databases or reviews on asthma and AD, with a stronger correlation observed as gestational age decreases 6, [15][16][17] . Although beyond the scope of this study, the possible etiology of prematurity-associated asthma is multifactorial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, prematurity was positively related to the future development of asthma and AR in the pediatric population, while being protective against the development of AD. These results are consistent with ndings from other nationwide databases or reviews on asthma and AD, with a stronger correlation observed as gestational age decreases 6, [15][16][17] . Although beyond the scope of this study, the possible etiology of prematurity-associated asthma is multifactorial.…”
Section: Discussionsupporting
confidence: 91%
“…Factors may include the underdevelopment of the airway, antibiotic use, increased risks for viral respiratory infections, decreased breastfeeding, and altered microbiota 18 . On the other hand, the cause for the association of prematurity with a lower risk of AD was proposed to be the increased permeability of their immature skin, early antigen exposure in the neonatal intensive care unit (NICU), and altered skin microbiota 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the lung functions of pretermborn children decreased significantly at school age [7][8][9][10]. In addition, various studies investigating atopy in premature children have been conducted, some studies have shown that atopy is a reduced risk factor, while others have shown that there is no relationship between gestational age and atopy [10][11][12][13][14][15][16]. In this study, it was aimed to determine the respiratory functions and atopy susceptibility of preterm and term patients hospitalized for respiratory distress in the neonatal period and healthy children and to compare the results.…”
Section: Introductionmentioning
confidence: 99%